Cultura institucional y perspectiva de género en las corporaciones de seguridad pública en México (2021)
The gender gap is not only observed in those institutions that historically have had a male labor tradition. Although the presence and participation of women in public spaces is currently more visible, positions of power, command or hierarchy continue to be assigned more favorably to the male gender, who hold more leadership positions than the female gender. It is essential to position within the state and social agenda, the construction of an institutional culture based on the gender perspective and the mainstreaming of labor conditions and equal access in the state public administration, in order to identify areas of opportunity where it is required to make a balance and a diagnosis on the behaviors or practices that encourage inequality, as is the case in police forces.